Survival of adults with systemic autoimmune rheumatic diseases and pulmonary arterial hypertension after lung transplantation. (13th February 2018) - Bernstein, Elana J; Bathon, Joan M; Lederer, David J
Abstract: Objectives: Pulmonary arterial hypertension (PAH) is a major cause of morbidity and mortality in adults with systemic autoimmune rheumatic diseases (ARDs). The aim of this study was to determine whether adults with ARDs and PAH on right-sided heart catheterization (ARD-PAH) have increased mortality following lung transplantation compared with those with PAH not due to an ARD. Methods: We conducted a retrospective cohort study of 93 adults with ARD-PAH and 222 adults with PAH who underwent lung transplantation in the USA between 4 May 2005 and 9 March 2015 using data from the United Network for Organ Sharing. We examined associations between diagnosis and survival after lung transplantation using stratified Cox models adjusted for potential confounding recipient factors. Results: Among adults undergoing lung transplantation in the USA, we did not detect a difference in the multivariable-adjusted mortality rate between those with ARD-PAH and those with PAH [hazard ratio 0.75 (95% CI 0.47, 1.19)]. Conclusion: The presence of an ARD was not associated with increased mortality after lung transplantation in adults with PAH.